2012
DOI: 10.12659/aob.882755
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between predisposition to work under different energy modes and individual characteristics of skilled wrestlers’ tactical approach

Abstract: Background It is known that athletes have different development levels of individual aspects of energy capacity. This is determined to a great extent by the unique, innate physiology of the individual. Therefore, these differences may influence a wrestler's individual inclinations to a specific manner of action during competition. The objective of this study was to reveal the relation between individual predisposition to work under different energy modes as indicated by particular aspects of specialized physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…A deficit of studies on the analysis of successive training cycles and changes in them was found [28]. Considering that it has been shown that properly arranged energy relationships based on properly trained wrestlers' capacities are one of the determinants of the rate of recovery of high-intensity training capacity and that body composition is significantly related to the level of aerobic capacity of wrestlers [29,30]. The authors decided to analyze the associations of body composition with the level of aerobic capacity and the level of post-exercise restitution, as well as the changes that occur during the period of training camp before the main competition-the European Cadet Championships.…”
Section: Introductionmentioning
confidence: 99%
“…A deficit of studies on the analysis of successive training cycles and changes in them was found [28]. Considering that it has been shown that properly arranged energy relationships based on properly trained wrestlers' capacities are one of the determinants of the rate of recovery of high-intensity training capacity and that body composition is significantly related to the level of aerobic capacity of wrestlers [29,30]. The authors decided to analyze the associations of body composition with the level of aerobic capacity and the level of post-exercise restitution, as well as the changes that occur during the period of training camp before the main competition-the European Cadet Championships.…”
Section: Introductionmentioning
confidence: 99%